Hydrosocial territories in Costa Rica: water concessions and conflicts - Gutiérrez Arguedas, Alberto (2026)
One of the central concepts in studies of the political ecology of water is that of hydrosocial territories. This is the analytical matrix that allows us to elucidate, in specific geographical contexts, the unequal power relations that shape certain political-institutional and territorial arrangements related to water, as well as the resulting socio-environmental conflicts. This paper aims to examine the hydrosocial territories in two geographically situated study areas, in the Central Pacific and the Southern Zone of Costa Rica. Two complementary approaches are used, one quantitative and the other qualitative: (i) the systematization of water use concessions and (ii) the study of the causes, meanings and impacts of socio-environmental conflicts over water. Among the study´s main findings, it identified a significant monopolization of water concessions for extractive activities (agricultural, agro-industrial and hydroelectric production), benefiting economically powerful actors at local, national and global levels. In this context, socio-environmental conflicts over water are interpreted as a response to water injustice, from which community-based socio-environmental organizations have emerged, challenging dominant water management policies and discourses.